Qualitative Insights into Speaking Skill Development Through Debating - Ginting , Hestika; L.Simanjuntak, Winaria Peggy (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
Speaking skill is one of the most challenging aspects of English as a Foreign Language (EFL) learning. This qualitative study investigates how debating activities have an effect on undergraduate students’ speaking skill development. Seven undergraduate students majoring in English Literature in Sekolah Tinggi Bahasa Asing Persahabatan Internasional Asia (STBA-PIA) participated in semi-structured interviews. Thematic analysis revealed four major themes: (1) difficulties in speaking English, including vocabulary, grammar, pronunciation, and anxiety; (2) improvement in speaking skills through debating, particularly fluency, vocabulary, pronunciation, and grammar; (3) enhancement of confidence, motivation, and anxiety management; and (4) development of argumentation and critical thinking skills. The findings imply that debates are an effective pedagogical strategy fostering language skills, cognitive, and socio-emotional development. Implications for teaching include integrating structured debates in EFL classrooms to improve speaking skills and promote learner autonomy. The study also shows the importance of qualitative methods to better understand learners’ perceptions and experiences in language learning.